Identification of Factors Affecting Cadets' Self-Adjustment in Academic and Non-Academic Contexts - Farhan Muttaqin, A; Robbi Fathoni, Achmad; Putra Malo Sitorus, Apridho; Felix Betani Silalahi, Carlos; Yudyadinata Haritama, I Made; Eryanto Putra, Ridho (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Self-adjustment is essential for cadets entering state-run educational institutions with strict discipline. Adaptation involves managing academic pressures and non-academic challenges, such as physical training, dormitory life, and hierarchical systems. Internal factors like emotional maturity and external support significantly influence adaptation. However, holistic studies on cadet adjustment remain limited. Objective: This study aims to analyze essential factors shaping cadets' self-adjustment within a strict semi-military education environment. Method: Using a qualitative approach, the research draws upon in-depth interviews to identify cadets' adaptation strategies toward academic pressure and dormitory routines. Result and Discussion: Findings indicate Academic Conflict (27%) as the primary challenge, addressed through Strategies and Character (38%), with peer support enhancing resilience. Vision and Mentality (27%) highlight that successful adjustment relies on Character Maturity and holistic balance beyond academics. Conclusion: Cadet adaptation is a transformative process where environmental pressures foster social networks and integrity, aligning with civil service ideals